Matka Maria (Skobcowa) w świecie idei Władimira Sołowiowa - Laszczak, Wanda (Rusycystyczne Studia Literaturoznawcze, 2016)
This paper covers the reflections of Mother Maria on Vladimir Solovyov’s key philosophical concepts — including Allunity and Panunity, Sophia, Divine Humanity, good and evil, theocracy, and the Russian Idea — included in Światopogląd Władimira Sołowiowa [Vladimir Solovyov’s Weltanschauung]. It also hints her judgement on the role and legacy of the author of A Story of Anti-Christ within the history of philosophy. Skobstova’s conviction of persisting impact of Solovyov’s philosophy is rooted in his task to prevail over the destructive tendency present in European philosophy, which has resulted in the crisis of understanding of the world. Skobtsova analyses and comments upon Solovyov’s thought not as a distanced scholar of Russian culture, but rather as an apprentice following her master, who does not restrain from engaging in polemics with him. Her turn to verification and re-interpretation is especially visible in those comments which are concerned with the particular aspects of Solovyov’s concept of the Russian Idea. The starting point for Skobtsova’s analysis is provided by the events of the October Revolution. As the paper claims, the confrontation of Solovyov’s thought with the post-1917 reality has not reached success. Solovyov is convinced that that the mission of the Russian czar is to unify humanity, while the Church of the future will reach its centre in the person of a pope in Rome, rather than in the Russian Orthodox Church, which should deprive itself of the claim for supremacy and singularity; against him, Mother Maria reminds us that the czar abdicated in 1917, while the Orthodox Church — after reinstating the Patriarchy — began to restore. The Russian Idea, as Skobtsova argues, has not found a confirmation in the Russian nation and happened to fail. With regard to those facts, she reaches a premise confirming her view that the way of future development of humanity — which aims at realising God’s will — can be only indicated by the Orthodox Russia with its religion of Divine Humanity.